Incidence And Characteristics Intradialytic Hypertension Among Chronic Hemodialysis Patients Caused By Chronic Kidney Failure At Rsmh Palembang Period November 2018 - Ghina Kartika; Suprapti Suprapti; Irfannuddin Irfannuddin (Majalah Kedokteran Sriwijaya, 2019)
Intradialytic hypertension have 5 – 15 % incidence among chronic hemodialysis patients caused by chronic kidney failure. But, mostly medical practician focused only at intradialytic hypotension than intradialytic hypotension as the most frequent cardiovascular complications. Intradialytic hypertension itself is one of the cause of mortility and morbidity hemodialytic patients, that’s why patients should be aware of  intradialytic hypertension. This study aims to know the frequencies of patients with intradialytic hypertension at RSMH Palembang period November 2018, and the characteristics of the patients based on patients sosiodemography, etiology of their chronic kidney disease, their hemodialysis period, and their activity during hemodialysis.Method : This study is descriptive analysis with total sampling, with primary data from patients blood pressure measurement, and interview with patients in hemodialysis installation at RSMH Palembang. In this study,305 samples were found, with 198 patients fulfilled inclusion criteria. Result : The result of this study shows that from 198 subjects, there are 116 (58,6%) of them who suffer intradialytic hypertension. Intradialityc hypertension patients mostly in the group age 46 – 65 years old (51%), male patients (61.2%) are more likely develop intradialytic hypertension than female patients (38.8%), patients with high educational backgroud also more likely to develop this complications. Their chronic kidney diseases cause are mostly hypertension (67,2%), and the higher activities patients during hemodialysis also more likely to develop intradialytic hypertension.Conclusion : Patients in hemodialysis installation at RSMH Palembang with intradialytic hypertension are more than the patients without the intradialytic hypertension (normotension and intradialytic hypotension patients are included), patients in old age group, male patients, and the higher patients activities during hemodialysis process the more highly patients develop intradialytic hypertension as complication.